Endobronchial ultrasound: beyond nodes and masses. Issue 4 (24th September 2015) - Joshi, Sharad; Talwar, Deepak; Dogra, Vikas
Abstract: Pulmonary embolism (PE) is a life‐threatening condition with varied presentation and, therefore, poses clinical challenge for early diagnosis and proper management without which it carries high mortality. Previous studies on the role of endobronchial ultrasound (EBUS) in diagnosis of PE were carried out after PE was already diagnosed by computed tomography pulmonary angiography. We report a case of massive PE with shock, promptly diagnosed with bed side EBUS – Doppler study, as patient's clinical condition did not allow conventionally proposed diagnostic algorithm. Abstract : We report a case of massive pulmonary embolism with shock, promptly diagnosed with bed side EBUS – doppler study as patient's clinical condition did not allow conventionally proposed diagnostic algorithm.